THE INFLUENCE OF FINANCIAL DISTRESS, AND EARNING MANAGEMENT ON TAX AVOIDANCE WITH GOOD CORPORATE GOVERNANCE AS A MODERATION VARIABLE IN REGISTERED INFRASTRUCTURE SECTOR COMPANIES ON THE INDONESIAN STOCK EXCHANGE YEAR 2019 - 2021 - Busyaib Syamsul Sirot; Enggar Diah Puspa Arum; Wiralestari Wiralestari (Transpublika Publisher, 2024)
This study seeks to investigates the relationship between financial distress, earning management, and tax avoidance within the context of registered infrastructure sector companies on the Indonesian Stock Exchange during the period from 2019 to 2021. The research population consists of infrastructure companies listed on the Indonesian Stock Exchange during the specified timeframe. The study employs the Judgment sampling method to select a representative sample that adheres to predefined criteria, resulting in a dataset comprising 66 observations. The research employs multiple linear regression analysis and moderated regression analysis methods to rigorously test the hypotheses. The findings of this study reveal that both financial distress and earning management significantly influence tax avoidance in the infrastructure sector companies. However, the role of good corporate governance as a moderating variable is explored, and the results suggest that it does not effectively moderate the influence of financial distress and earning management on tax avoidance. These results shed light on the complex dynamics within the Indonesian infrastructure sector and provide valuable insights for policymakers, researchers, and practitioners.